Experience and Self–management on Volume Overload in Patients with End–Stage Renal Disease undergoing Hemodialysis - Samrannet, Wanwisa; Kor–issaranuphab , Nittaya; Duangmartpol, Kachanakan (Medical Journal of Sakon Nakhon Hospital, 2024)
This qualitative research aimed to study the self–management on volume overload in patients with end–stage renal disease undergoing hemodialysis. The Heidegger’s hermeneutic phenomenological approach was applied in this study. The informants were patients with end–stage renal disease undergoing hemodialysis. They had an experience of volume overload a year ago. Twenty informants were purposively recruited at the hemodialysis unit in Mahasarakham hospital. This study was conducted from June to July 2022. The data were collected using individual in–depth interviews. The data trustworthiness was established following Lincoln and Guba’s criteria. The data were analyzed by content analysis. The findings of this study were composed of 4 themes including: 1) Giving the meaning of volume overload, kidney degeneration and edema 2) Self–management of volume overload, a fluid restriction, diet control, taking medicine and mental self–management 3) The effects of volume overload, physical aspect; dyspnea, orthopnea and mental aspect; fear/ anxiety, boredom and uncertainty of life and 4) Factors affecting volume overload, self–management, healthcare workers and caregivers. The findings could be applied to other patients for self–care management to prevent the volume overload and used as information for program development to enhance patients’ awareness in changing their lifestyles and self–management and for promoting the patients’ self–care behaviors as appropriate and sustainable.